Effect of different types of aramid fibres on mechanical and thermal properties of nano-cellulose composites for vehicle applications. (8th November 2010) - Gabr, Mohamed H.; Matsuoka, Kaho; Okubo, Kazuya; Fujii, Toru
Natural-fibre composites have been embraced by car manufacturers and suppliers for door panels, seat backs, headliners, package trays, dashboards, and interior parts. Natural fibres offer such benefits as reductions in weight, cost, and CO2. Eco-friendly green/composites were fabricated from nano-cellulose and bacterial cellulose (BC) reinforced by aramid fibres (AF). The purpose of this study is to propose an effective form of AF as reinforcement in cellulose composites instead of expensive conventional materials for interior car parts. Technora (AFT) and Kevlar29 (AFK) with fibre length 1 mm and 5 mm (AFT1, AFT5, AFK1, and AFK5) were used as reinforcement. These materials were characterised by different techniques, namely SEM, TGA, tensile, bending, and hardness tests. All composites showed good dispersion for fibres and strong adhesion between the fibres and the matrix. The composites prepared with BC displayed better flexural and Young's modulus, hardness and significant decrease for the coefficient of thermal expansion.